Declining populations in one of the last refuges for threatened mammal species in northern Australia. (24th March 2018) - Davies, Hugh F.; McCarthy, Michael A.; Firth, Ronald S. C.; Woinarski, John C. Z.; Gillespie, Graeme R.; Andersen, Alan N.; Rioli, Willie; Puruntatameri, José; Roberts, Willie; Kerinaiua, Colin; Kerinauia, Vivian; Womatakimi, Kim Brooks; et al.
Abstract: Australia has contributed a disproportionate number of the world's mammal extinctions over the past 200 years, with the greatest loss of species occurring through the continent's southern and central arid regions. Many taxonomically and ecologically similar species are now undergoing widespread decline across the northern Australian mainland, possibly driven by predation by feral cats and changed fire regimes. Here, we report marked recent declines of native mammal species in one of Australia's few remaining areas that support an intact mammal assemblage, Melville Island, the largest island off the northern Australian coast. We have previously reported a marked decline on Melville Island of the threatened brush‐tailed rabbit‐rat ( Conilurus penicillatus ) over the period 2000–2015, linked to predation by feral cats. We now report a 62% reduction in small mammal trap‐success and a 36% reduction in site‐level species richness over this period. There was a decrease in trap‐success of 90% for the northern brown bandicoot ( Isoodon macrourus ), 64% for the brush‐tailed rabbit‐rat and 63% for the black‐footed tree‐rat ( Mesembriomys gouldii ), but no decline for the common brushtail possum ( Trichosurus vulpecula ). These results suggest that populations of native mammals on Melville Island are exhibiting similar patterns of decline to those recorded in Kakadu National Park two decades earlier, and across the northern Australian mainland more generally. Without the implementation of effective management actions, these species are likely to be lost from one of their last remaining strongholds, threatening to increase Australia's already disproportionate contribution to global mammal extinctions.